ЕВРОПЕЙСКИЕ БЮДЖЕТНЫЕ АВИАПЕРЕВОЗЧИКИ: ИСТОРИЯ, БИЗНЕС-МОДЕЛИ И РОЛЬ В ТУРИЗМЕ (Географический вестник=Geographical bulletin, 2017)
Рассмотрены малобюджетные пассажирские авиалинии и авиаперевозчики- лоукостеры (LCC). Дана характеристика этапов развития и современных типов LCC: чартерные, традиционные, сервисные, региональные. Представлены география европейской маршрутной сети и типичная бизнес-модель LCC, сформулированы ее основные отличия от бизнес-модели классических авиаперевозчиков. Показана роль LCC в развитии туризма.К л ю ч е в ы е с л о в а: лоукостер (LCC); бюджетная авиакомпания; классическая авиакомпания; маршрутная сеть; бизнес-модель.EUROPEAN BUDGET LOW-COSTERS: HISTORY, BUSINESS MODEL AND ROLE IN TOURISM The article is devoted to the problem of the role of low-cost carrier, low-cost airline (LCC) in the development of tourism. The characteristics of the main periods of low-cost carrier development are considered, and modern types of low-cost are examined: the charter, traditional, service and regional ones. The geography of the European route net is presented. A typical business model of LCC is regarded in comparison to business models of traditional airline carriers.K e y w o r d s: low-cost carrier (LCC); budget low-coster; airline of traditional; route net; business model.